The Effect of Technological Innovation, Sustainable Creativity, and Family Environment on Entrepreneurial Intention Mediated by Self-Efficacy among Undergraduate Students of Academic Year 2021/2022 at Universitas Mercu Buana, Meruya Campus, Jakarta - Sri Winarsih, Eka (IJOSMAS, 2025)
This study aims to analyze the influence of technological innovation, sustainable creativity, and family environment on entrepreneurial intention mediated by self-efficacy among undergraduate students at Universitas Mercu Buana, Meruya Campus. The research design employs a quantitative approach with explanatory methods using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The study population consisted of 18,458 undergraduate students, with a sample of 393 respondents selected using Slovin's formula and purposive sampling. Data were collected through online questionnaires and analyzed using SmartPLS 4.0. The results show that technological innovation, sustainable creativity, and family environment have a positive and significant effect on entrepreneurial intention, both directly and indirectly through self-efficacy. Furthermore, self-efficacy significantly mediates the relationship between independent variables and entrepreneurial intention. These findings support the Theory of Planned Behavior (TPB) and contribute to achieving Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation, and Infrastructure), and SDG 12 (Responsible Consumption and Production). The study highlights the importance of higher education institutions in strengthening entrepreneurial ecosystems through technology, creativity, and family support.